Parents' Policy in Developing the Numerical Literacy of Their Teenage Children: A Descriptive Qualitative Study - Fonda, Aulia; Ramadhan, Katon Agung; Firdaus, Muh Wildanul; Junianto (Jurnal Pendidikan Matematika, 2025)
The Program for International Student Assessment (PISA) states that the literacy and numeracy of students in Indonesia are in the low category. Indonesia scored 366 and ranked 68 out of 81 countries. Previous research discussed parental involvement in developing early childhood literacy. This study aims to investigate parents' policies in developing numerical literacy in adolescent children. This study used a qualitative descriptive method. Data were collected through questionnaires filled in by parents and interviews related to the interaction between parents and children in the context of numerical literacy. There are 9 respondents, namely mothers of adolescent children who will be studied. The results showed that parents' policies in supporting numerical literacy include providing direct support in learning mathematics, providing adequate learning resources, and implementing daily activities related to numeracy. Obstacles to implementing this policy include parents' limited time, children's lack of interest in numerical literacy, and others. This study concludes that parents view the development of numerical literacy as “very important”. Parents' policies support the development of numerical literacy in adolescent children by involving children in financial management and playing an active role in their activities of adolescent children.